2007
DOI: 10.1007/s00405-007-0305-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-syndromal round window atresia: an autosomal dominant genetic disorder with variable penetrance?

Abstract: Round window atresia can be seen in association with syndromal anomalies such as mandibulofacial dysostosis, Mondini type anomalies or cretinism, or with extensive otosclerosis. Non-syndromal round window atresia is extremely rare and until today there is no proof whether non-syndromal round window atresia can be inherited. We present two family members with non-syndromal round window atresia. Based on this case and on an extensive literature review, we discuss the possible ways of sound transmission with roun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Furthermore, occlusion of the round window is thought to induce a hearing loss (108, 109). In the series by Silverstein et al, hearing loss was the only subjective survey measure that did not improve after round window reinforcement (106), others have reported a conductive hearing loss (105), and additional series of patients undergoing round window reinforcement by some of the authors have shown a mild hearing loss with this surgery in the non-dehiscent ear (110, 111).…”
Section: Treatmentmentioning
confidence: 99%
“…Furthermore, occlusion of the round window is thought to induce a hearing loss (108, 109). In the series by Silverstein et al, hearing loss was the only subjective survey measure that did not improve after round window reinforcement (106), others have reported a conductive hearing loss (105), and additional series of patients undergoing round window reinforcement by some of the authors have shown a mild hearing loss with this surgery in the non-dehiscent ear (110, 111).…”
Section: Treatmentmentioning
confidence: 99%
“…This factor has been studied largely by clinical observation and rarely in controlled experiments in animal models. In clinical settings, the effects of the round-window closure were unclear (17,18), ranging from no change in auditory thresholds to mild or moderate conductive hearing loss (19). The effects of ovalwindow fixation were demonstrated in patients with otosclerosis (i.e., stapedial footplate fixation), who showed a deterioration in air-conduction threshold with minimal to no change in bone conduction (18).…”
mentioning
confidence: 98%
“…[28] In human participants, hearing could be elicited when vibratory stimuli were applied to soft tissues such as the eye, neck, back, and thorax. [243132] These findings, as well as clinical observations showing preserved BC thresholds in the absence of two mobile windows in the inner ear,[3334] support the existence of a mechanism that is different from AC and osseous BC. [35]…”
Section: Discussionmentioning
confidence: 76%